133 A DERMATOLOGIC MANIFESTATION OF MUCORMYCOSIS IN A PEDIATRIC PATIENT WITH ACUTE LYMPHOBLASTIC LEUKEMIA. Issue 1 (1st January 2007) - Singleton, T.; Gardner, R.; Thom, G.
Abstract : We describe a patient with invasive necrotizing cutaneous mucormycosis caused by Rhizopus . The patient is a 15-year-old female diagnosed with high-risk acute lymphoblastic leukemia (ALL), on chemotherapy for 1 year. She presented with a small painless erythematous papule of the lower extremity. She was started on voriconizole, and the small erythematous papule progressed to large necrotic lesion with surrounding erythema and tenderness. Débridement was performed, and microscopic examination and culture revealed mucormycosis. The patient was immediately started on amphotericin B, and after 8 weeks of therapy, all subsequent fungal cultures were negative. She continued with chemotherapy with resulting intermittent neutropenia. Six months after débridement and antifungal therapy, she had persistent poor wound healing with intermittent and superinfection with Pseudomonas . Appropriate antibiotic therapy was started without delay, and following count recovery, a second débridement and skin grafting were performed by plastic surgery. Following the second débridement and skin grafting, she had a complete recovery. Clinicians should have a very high index of suspicion that patients with leukemia, or other immunocompromised states, presenting with cutaneous lesions may have cutaneous manifestations of mucormycosis. These patients should be evaluated promptly with tissue biopsy, aggressive débridement, appropriate cultures, and empiric therapy with amphotericin B without delay. Isolated fungal soft tissue infections are uncommon but may result in significant morbidity and mortality in the immunocompromised patient. A second débridement with skin grafting by a skilled plastic surgeon should be highly considered in this patient population.